EVALUATION OF STUDENT SERVICES, SCHOOL CULTURE, AND PARTNERSHIPS IN ENHANCING THE QUALITY OF ISLAMIC EDUCATION: A CASE STUDY - Rhani Fuji Lestari; Mulyawan Safwandy Nugraha (STKIP Subang, 2026)
This study aims to integratively analyze the role of student services, school culture based on Islamic values, and partnerships among schools, parents, and the community in improving the quality of Islamic education. A qualitative case study was conducted at Madrasah Tsanawiyah Assuruur using semi-structured interviews, participatory observation, and documentation involving principals, teachers, students, and parents selected through purposive and snowball sampling. Data were analyzed using the interactive model of Miles and Huberman combined with thematic analysis. The findings reveal four key aspects: the dual role of teachers in academic and character development, the strong internalization of religious culture, communicative yet non-participatory partnerships, and limited integration across educational components. These results indicate that educational quality is shaped by dynamic interactions among services, culture, and partnerships. The study contributes to an integrative framework for improving Islamic education quality through systemic and sustainable approaches. Keywords: Islamic education quality; qualitative study; school culture; student services; school partnership